Pengaruh Karakteristik Perusahaan, Kualitas Audit, dan Kepemilikan Institusional Terhadap Asimetri Informasi - Septian, Rifki; Setyadi, Edi Joko; Santoso, Suryo Budi; Inayati, Nur Isna (Jurnal Ecogen, 2024)
This research to determine the influence of company characteristics, audit quality, and institutional ownership on information asymetry. The reseacrh method used is aquantitative method. The population in this study are manufacturing companies in the consumer goods and industrial sector listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. The sampling technique in this research uses a purposive sampling technique with a total of 129 data. The data analysis method used is panel data regression analysis, using E-Views 12 software. Based on the results of panel data regression analysis testing, it is known that company age and audit quality have a significant effect to information asymetry. Meanwhile, company size, leverage profitability and institutional ownership have no effect on information asymetry.